Early bactericidal activity of rifabutin versus that of placebo in treatment of disseminated Mycobacterium avium complex bacteremia in AIDS patients. - Dautzenberg, B (1996)
Rifabutin, 600 mg/day, was compared with a placebo in the early treatment of culture-proven Mycobacterium avium bacteremia in patients with AIDS. Following 14 days' treatment, bacteriological success, defined as a negative culture or a reduction in the number of CFU of M. avium organisms per milliliter of blood by a factor of > or = 0.5 log from the baseline, was observed in 7 of 10 (70%) evaluable rifabutin patients and in 1 of 13 (8%) evaluable placebo patients (P = 0.002). Rifabutin is active against M. avium as a single agent and can make a significant contribution to combination regimens for the treatment of disseminated M. avium infection in AIDS patients.